Retraction: How COVID-19 Brought Indian Wedding Industry to a Halt? - Gupta, Ritik Ranjan; Arya, Ravi Kumar; Kumar, Jatin; Shubham, Tanay (JINAV: Journal of Information and Visualization, 2020)
This paper was retracted by JINAV Journal on 03 February 2021. This paper was published in another journal (International Journal of Management and Humanities (IJMH), Volume 5 Issue 5, January 2021).